Wear performance of Ti-6Al-4 V titanium alloy through nano-doped lubricants - Etri, Hamza E. L.; Singla, Anil Kumar; Özdemir, Mehmet Tayyip; Korkmaz, Mehmet Erdi; Demirsöz, Recep; Gupta, Munish Kumar; Krolczyk, J. B.; Ross, Nimel Sworna (Archives of Civil and Mechanical Engineering, 2023)
Titanium and its alloys are widely utilized in the biomedical sector, they still exhibit poor tribological properties and low wear resistance when employed against even weaker substances. The poor hardness, instability, high coefficient of friction, low load-carrying capacity, and insufficient resistance to not only abrasive but also adhesive wear are further disadvantages of titanium alloys. The focus of this investigation is on the tribological performance of Ti-6Al-4 V alloy in contact with WC carbide abrasive balls when subjected to nanodoped cooling and lubrication conditions. Tribological experiments were executed on Ti-6Al-4 V flat samples using a ball-on-flat tribometer in dry hybrid graphene/boron nitride combination nanoparticles (MQL, nano-3), nanographene with MQL (nano-1), and boron nitride with MQL (nano-2) conditions. After that, the most significant tribological characteristics were investigated, including volume loss, friction coefficient, wear rate, and micrographic structures. The outcomes also demonstrated that the hybrid nanoparticle situation experienced the least amount of volume loss.